El bienestar de la cultura - Ríos, Félix J. (Romanica Silesiana)
This paper deals with the cultural conflict in Western societies throughout the past few decades. As Vargas Llosa says, present-day culture is reduced to a practice that tends to get rid of our concerns, and that makes us live a kind of fiction or game. We must denounce the complicity of the big names that represent the culture in the postmodern world. Many intellectuals refuse to discuss it, and prefer to live on the revenues generated by the industry. The market has become a cultural expression. The responsibility lies in senders and receivers. Consumption of these pseudo-cultural products no longer causes shame. This conflict is evident in the so-called digital literature (not to be confused with digitized literature) which creates a hybrid product that is based on superficiality, simulation and spectacular sign. Present-day literature responds to the force of the image with the misappropriation of the movie phenomenon. In the same way that the neo-classicists denounced the Baroque excess, today we can, with absolute legitimacy, express our astonishment at the abandonment of literary essence, which is the act of reading, and the empowerment of other elements (visual and auditory) in products which we continue to call “literary”. We must find a way out of the dilemma that occurs and answer the question of whether culture is an idea, a feeling, a brain mechanism for progress, or a new consumer item that serves to hide our grief, our doubts and our questions. Key words: Culture, digital world, globalization, literature.